A safe place of one's own? Exploring practice and policy dilemmas in child welfare practice with families waiting for adequate and secure housing. Issue 6 (2nd November 2022) - Sen, Robin; Smeeton, Joe; Thoburn, June
ABSTRACT: As in many European states, a shortage of housing in England has resulted in some families who are 'waiting for' adequate and secure housing in England while also having the 'weight of' their children being placed outside their care hanging over them. This paper reports on the development of a practice guidance document that included an online survey with 38 children's social services practitioners in England regarding their practice experiences of responding to family homelessness. Findings suggest the complexity of the issue of family homelessness and implicitly highlight its neglect within contemporary research and policy in the UK. Homeless families are caught between the constraints of housing shortages and the complexity of the needs underpinning their homelessness. Despite these constraints, social work practice has an important role to play in providing, or facilitating families' pathway to, housing advocacy and advice. Most importantly of all, social work practice can maximise families' access to statutory family support provision so that families can be helped to remain together wherever this is safely possible. Suggestions for practice, policy, and research development are outlined.